The anatomist anatomis'd: an experimental discipline in Enlightenment Europe - Cunningham, Andrew (The history of medicine in context, 2010)
"This awful subject" -- "Merit is sure of its reward" : careers and courses -- Experimental anatomy and its sub-disciplines -- Human bodies : getting, keeping, picturing, publishing, arguing -- Animal bodies and comparative anatomy -- The end of old anatomy